Primary prophylaxis of variceal bleeding in children and the role of MesoRex Bypass: Summary of the Baveno VI Pediatric Satellite Symposium. Issue 4 (23rd October 2015) - Shneider, Benjamin L.; de Ville de Goyet, Jean; Leung, Daniel H.; Srivastava, Anshu; Ling, Simon C.; Duché, Mathieu; McKiernan, Patrick; Superina, Riccardo; Squires, Robert H.; Bosch, Jaime; Groszmann, Roberto; Sarin, Shiv K.; et al.
Abstract : Approaches to the management of portal hypertension and variceal hemorrhage in pediatrics remain controversial, in large part because they are not well informed by rigorous clinical studies. Fundamental biological and clinical differences preclude automatic application of approaches used for adults to children. On April 11‐12, 2015, experts in the field convened at the first Baveno Pediatric Satellite Meeting to discuss and explore current available evidence regarding indications for MesoRex bypass (MRB) in extrahepatic portal vein obstruction and the role of primary prophylaxis of variceal hemorrhage in children. Consensus was reached regarding MRB. The vast majority of children with extrahepatic portal vein obstruction will experience complications that can be prevented by successful MRB surgery. Therefore, children with extrahepatic portal vein obstruction should be offered MRB for primary and secondary prophylaxis of variceal bleeding and other complications, if appropriate surgical expertise is available, if preoperative and intraoperative evaluation demonstrates favorable anatomy, and if appropriate multidisciplinary care is available for postoperative evaluation and management of shunt thrombosis or stenosis. In contrast, consensus was not achieved regarding primary prophylaxis of varices. Although variceal hemorrhage is a concerning complication of portal hypertension in children, the first bleed appears to be only rarely fatal and the associated morbidity has not been well characterized. Conclusion : There are few pediatric data to indicate the efficacy and safety of pharmacologic or endoscopic therapies as primary prophylaxis or that prevention of a sentinel variceal bleed will ultimately improve survival; therefore, no recommendation for primary prophylaxis with endoscopic variceal ligation, sclerotherapy, or nonspecific beta‐blockade in children was proposed. (Hepatology 2016;63:1368–1380)